Gastric acid challenge of lithium disilicate-reinforced glass-ceramics and zirconia-reinforced lithium silicate glass-ceramic after polishing and glazing-impact on surface properties - Hjerppe Jenni; Shahramian Khalil; Rosqvist Emil; Lassila Lippo VJ; Peltonen Jouko; Närhi Timo O (SPRINGER HEIDELBERG, 2025)
Objectives: To investigate the impact of simulated gastric acid on the surface properties of lithium disilicate-reinforced glass-ceramics and zirconia-reinforced lithium silicate glass-ceramic after certain polishing and glazing procedures.
Materials and methods: Four different types of square-shaped specimens (10 × 10 × 2 mm3, n = 13) were manufactured: lithium disilicate-reinforced glass-ceramic milled and polished (LDS-P); milled, polished, and glazed (LDS-PG); milled, glazed, and no polishing (LDS-G); and milled and polished zirconia-reinforced lithium silicate glass-ceramic (ZR-LS). Specimens were immersed in hydrochloride acid (HCl 0.06 M, pH 1.2) to simulate gastric acid irritation and stored in the acid for 96 h in 37 °C. Specimen weight, surface gloss, Vickers surface microhardness and surface roughness (Ra, Rq, with optical profilometer), and surface roughness on nanometer level (Sq, Sal, Sq/Sal, Sdr, Sds with atomic force microscope) were measured before and after the acid immersion.
Results: ZR-LS specimens lost significantly more weight after acid immersion (p = 0.001), also surface microhardness of ZR-LS was significantly reduced (p = 0.001). LDS-G and LDS-PG showed significantly lower surface roughness (Sa, Sq) values compared to LDS-P before (p ≤ 0.99) and after (p ≤ 0.99) acid immersion and ZR-LS after acid immersion (p ≤ 0.99).
Conclusions: Gastric acid challenge affects the surface properties of lithium disilicate-reinforced glass-ceramic and zirconia-reinforced lithium silicate glass-ceramic. Glazing layer provides lower surface roughness, and the glazed surface tends to smoothen after the gastric acid challenge.
Clinical relevance: Surface finish of lithium disilicate-reinforced glass-ceramic and zirconia-reinforced lithium silicate glass-ceramic has a clear impact on material's surface properties. Gastric acidic challenge changes surface properties but glazing seems to function as a protective barrier. Nevertheless, also glazing tends to smoothen after heavy gastric acid challenge. Glazing can be highly recommended to all glass-ceramic restorations but especially in patients with gastroesophageal reflux disease (GERD) and eating disorders like bulimia nervosa.